HMOVG: An Interactive Computer Program Based on the Huckel Molecular Orbital Model and Making an Extensive Use of Graphic Facilities - Michel Roch; Jean-Jacques Combremont; Jacques Weber (CHIMIA)
HMOVG (Hückel Molecular Orbital Vector General) is basically a Hückel Molecular Orbital (HMO) program making an extensive use of interactive graphic facilities provided by a calligraphic display system. Most of the input is made from a data tablet and the output is treated graphically on the display monitor. This enables the user to enter by a rough drawing the system to be calculated and then to visualize interactively the HMO electronic structure and wave functions.